Sistema de actividades para el mejoramiento de la habilidad de comprensión de lectura en alumnos de onceno grado a partir de un enfoque comunicativo - Bringuez Cuello, Alexis (Universidad Central “Marta Abreu” de Las Villas. Facultad de Cultura Física. Centro de Estudios de Cultura Física, 2002)
Teaching English as a foreign language, has for long been aimed at the development of habits, skills and knowle dge that allw the students to read and understand texts of a middling complexity in intermediate level.Experience has shown that the procedures used today to develop satisfactory reading comprehensión in our students do not correspond with the new teaching learning process from a communicative approach since they do not involve the other threes skills, that is, listening, speaking and writing.
Keywords: Sistema-habilidad-comprensión de lectura